Pineal Gland Morphology in Relation to Age and Season in Three Canidae Species - Kalinina, Svetlana; Ilyukha, Viktor; Uzenbaeva, Lyudmila (Journal of Morphological Sciences, 2019)
Introduction The aim of the present study was to determine the morphological features of the pineal gland in three closely related Canidae species (raccoon dog, Nyctereutes procyonoides Gray, 1834; silver fox, Vulpes vulpes L., 1758; and blue fox, Vulpes lagopus L., 1758) of different ages during the breeding (spring) and nonbreeding (winter) periods.Materials and Methods Histological analysis of the pineal glands of canids was performed.Results The morphological changes in the pineal gland detected in the current study are either age-associated, including increase in the reticular fibers and vascularization in the studied species, as well as increase in the amount of the protruding septae in the blue fox, or seasonally related, including an increase in the number and size of blood vessels. The present work reported two types of pigments: lipofuscin (primarily in the silver fox) and melanin (primarily in the raccoon dog and in the blue fox). The pineal gland in the blue fox is characterized by the ability to form corpora arenacea.Conclusions The present study provides the first insight into the morphological changes of the pineal gland in three closely related Canidae species of different ages during the breeding (spring) and nonbreeding (winter) periods, and showed some species-specific features of gland morphology. The aspects concerning the biogenesis of the calcium concretions and the factors influencing the accumulation of pigments need further investigation.
Keywords: canidae; compared anatomy; corpora arenacea; microscopic animal anatomy; pineal gland